Investigating Teacher Scaffolding in Live Online EFL Reading Beyond the Classroom - Ummi Nurul Maghfiroh; Zainuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigated the scaffolding strategies applied by a teacher during synchronous online EFL reading activities held outside the traditional classroom setting and explored students’ responses to the support provided during the sessions. A descriptive qualitative approach was employed in this research, involving one English teacher and ten members of an English Speaking Club who regularly joined online reading activities. The data were collected through observations, semi structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing procedures. The teacher used various scaffolding strategies during the online reading sessions, such as demonstrating reading strategies, asking guiding questions, explaining unfamiliar vocabulary, giving corrective and elaborative feedback, and encouraging interaction among students. These types of support helped students understand the reading materials more easily and motivated them to participate more actively during the learning activities. In addition, students showed behavioral, cognitive, and emotional involvement throughout the sessions. They joined discussions, answered questions, tried to understand the texts, and gradually became more confident and motivated during the learning process. The teacher’s supportive and interactive approach also contributed to creating a more comfortable and positive atmosphere during the online classes. Scaffolding helped students understand the reading materials more easily while also encouraging them to become more active, confident, and involved during the online reading sessions. In addition, flexible and responsive teacher support was important in maintaining students’ academic and emotional engagement throughout the learning activities. Keywords: Online EFL Reading, Reading Comprehension, Scaffolding Strategies, Student Engagement, Synchronous Learning